Professors – the new YouTube stars: education through Web 2.0 and social network. (1st January 2013) - Saurabh, Samant; Sairam, Ashok Singh
Social networking sites like Facebook, Twitter and YouTube have changed the way people live. Today we depend heavily on social networking sites for our day to day activities. This paper presents a case study where we research the effect of YouTube on education. We have studied one of YouTube's most famous education channel called Khan Academy, founded by a MIT graduate. It has a huge collection of around 3, 200 video lectures. We perform in-depth study of Khan Academy. We provide results regarding viewer-ship and popularity of these lectures by providing statistics on view count, age of videos, user comments and rating of videos. We also study viewer characteristics like age, gender and location distribution. Overall, we believe that the results presented here are crucial in understanding importance and relevance of social network for education system. The results provide valuable information to educationalists in better using the social media to facilitate quality education.